Reviving the golden rule : how the ancient ethic of neighbor love can heal the world - DeCort, Andrew D. (Downers Grove, IL : IVP Academic, 2025)
"The other is our neighbor-not our enemy. The charges to "love your neighbor as yourself" and to "do to others as you would have them do to you" are at the heart of Abrahamic faith. Theologian and ethicist Andrew DeCort argues that it is also at the heart of some of the most groundbreaking developments in human rights and the common good. Insightfully, Jesus taught neighbor-love and promised, "Do this and you will flourish." But Christians today are at high risk of ignoring or overthrowing the most daring teaching of Jesus's movement. Having heard it repeatedly and benefited immensely from its cultural effects, we have become dulled to neighbor-love's revolutionary power. In response, DeCort takes us on an expert tour of the ethics of neighbor-love from the ancient world to today. He unpacks how neighbor-love has challenged the oppressive power of othering and radically expanded our humanity. He showcases inspiring figures like Dietrich Bonhoeffer, Mother Teresa, and Oscar Romero, who courageously practiced neighbor-love with dehumanized others. He also highlights areas where Christians have betrayed neighbor-love and provides energizing guidance for how we can love our othered neighbors as ourselves today. In one of the only historical and constructive works on the ethics of neighbor-love, DeCort invites us to reclaim this ancient movement and to embody its revolutionary practice amidst our current crises for the healing of the world"-- Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Love -- Religious aspects -- Christianity; Interpersonal relations -- Religious aspects -- Christianity